Formalismo sintattico e text-languages (Atti del Sodalizio Glottologico Milanese, 2019)
The present article discusses the meaning and relevance of “syntactic formalisms” and of the theoretical frameworks of structural syntax when applied to the study of the Ancient Indo-European languages. Reference will be made to (1) the advantages of a hierarchic representation of constituency patterns and (2) the limits of application of theoretical concepts to languages that are only preserved in text-corpora. KEYWORDS: syntax, theoretical frameworks, formalism, Indo-European languages, text-languages